P-293 Loss of Star-related Lipid Transfer Domain Protein (StarD7) Induces Intestinal Epithelial Mitochondrial and Barrier Dysfunction and Increases Susceptibility to Colitis. (February 2017) - Hogan, Simon; Wu, David; Rosen, Michael; Yang, Li; Denson, Lee; Waggoner, Lisa; Weaver, Tim
Abstract : Background: The inflammatory bowel diseases (IBD) Crohn's disease (CD) and ulcerative colitis (UC) are chronic relapsing gastrointestinal (GI) inflammatory diseases that affect 1 to 1.5 million Americans and cause substantial morbidity and decreased quality of life. We have recently identified dysregulated expression of the protein, Star-related lipid transfer domain protein (StarD7) in colonic biopsy samples of inflamed UC patients. StarD7 is a steroidogenic acute regulatory protein-related lipid transfer domain containing protein that regulates intracellular non-vesicular trafficking of phosphatidylcholine (PC) to mitochondrial membranes and the nucleus and regulates cell proliferation, migration and differentiation. Methods: We generated intestinal epithelial-specific and global StarD7-deficient mice and employed Dextran sodium sulphate (DSS)-induced and IL-10-deficient models of colitis to define the importance of StarD7 in the susceptability to colitis phenotypes. We utilized lentiviral StarD7 knockdown intestinal epithelial cell lines to define the contribution of this molecule to intestinal epithelial mitochondrial function, barrier properties and pro-inflammatory cytokine production. Results: We generated intestinal epithelial-specific and global StarD7-deficient mice. We show that ShhCreStarD7fl/fl mice have altered homeostatic intestinal epithelial barrier dysfunction compared with WT mice (Resistance RT 167.1 ± 8.1 versus 125.5 ± 5.6 W·cm 2 ; mean ± SEM, P < 0.05; FITC-Dextran 4kDa Flux 2.7 ± 0.2 versus 4.4 ± 0.3 pg·mL·min −1 ; mean ± SEM, P < 0.01; WT versus ShhCreStarD7fl/fl, respectively). Notably, the dysregulation of intestinal epithelial barrier function was associated with altered TJ protein expression including Claudin-4 and claudin-5 and increased susceptibility to Dextran sodium sulphate (DSS)-induced colitis (histological score: 3.5 ± 0.9 versus 8.6 ± 1.0; mean ± SEM, P < 0.05; WT versus ShhCreStarD7fl/fl, respectively). In a series of in vitro experiments employing intestinal epithelial cell lines and siRNA StarD7 knockdown technology we identified novel critical functions for StarD7 in maintenance of (1) intestinal epithelial homeostatic mitochondrial function and (2) PPAR:RXR transcription factor function which culminates in preservation of TJ protein expression and intestinal epithelial barrier function. Moreover, we show that StarD7 knockdown in human intestinal epithelial cells promotes mitochondrial and ER stress which was associated with increased pro-inflammatory cytokine (IL-25, IL-33 and TSLP) production. Indeed, rescue of mitochondrial stress by pharmacological agonist rescued intestinal TJ expression and barrier function in vitro and in vivo. Conclusions: These data suggest that the PC-lipid transfer protein Stard7 is critical for intestinal epithelial mitchondrial function and maintenance of immune homeostasis.